Synthesis, Characterization and Application of Polyacrylamide Grafted Sago Strach for Coagulation and Flocculation Processes - M. Qudsieh, Isam Yassin (2006)
Graft copolymerization of polyacrylamide (PAm) onto sago starch (S.S), S.S-g-PAml, SS-g-PAm2, S.S-g-PAm3, and S.S-g-PAm4, were carried out by a free radical initiation using cerric ion (CAN)-induced redox polymerization technique at 30+1°C, and under nitrogen gas atmosphere by varying the amount of CAN and PAm. The copolymers produced were characterized by Fourier Transform Infrared Spectrophotometry (FT-IR), Thermogravimetric analysis (TGA), elemental and gravimetric analyses. The FT-IR spectra of the copolymers clearly indicated the presence of characteristic peaks of PAm and sago starch, which suggested that PAm had been successfully grafted onto the sago starch. TGA thermograms showed that the copolymerization products were made up of two different polymers. The copolymers of various percentages of yield and conversion were hydrolyzed with 0.5 M hydrochloric acid and the viscosity measurements of PAm produced from the copolymers were carried out using Ubbelohde viscometer. The average molecular weight of the side chains (Mv) of the copolymers were 5.6~105, 3.1 xlO5, 7.4 xlO5, and 2.0 x105 respectively and viscosity values were 251.97, 157.52, 314.43 and 110.02 mL/g respectively. A series of standard jar tests were conducted in order to evaluate the performance of the polymers prepared (S.S-g-PAm) in kaolin suspension. Among the graft copolymers, SS-g-PAml was selected based on the performance and sago starch content to be used in further experiments; further more, a series of standard jar tests were conducted to optimize the operation conditions of S.S-g-PAml in bringing down the turbidity of supernatant liquid of 200 NTU kaolin suspension by varying the following parameters: dosage, pH, speed of rapid mixing, time of rapid mixing, speed of low mixing, and time of low mixing. And the optimum conditions were found to be 0.5 mg/L, 6.3, 75 rpm, 4 minutes, 25 rpm, 5 minutes respectively. Substantial reduction of residual turbidity was achieved by S. S-g-PAm. Settling column analysis was established for S.S-g-PAml in low, medium to high (50, 200, 300 NTU, respectively) initial kaolin suspension turbidity. Initial turbidity and settling time were found to be one of the major factors in settling water coagulated with S.S-g- PAml. Residual turbidity was found to decrease with increasing settling time; the decrease was higher for kaolin water with higher initial turbidities. Four river samples were collected from two locations; two samples of low and medium to high turbidity (30.5, 780 NTU), respectively were collected from Hulu Langat Water Treatment Plant, and another two samples of the same level of turbidity (low and medium to high turbidity) (68 and 450 NTU), respectively were collected from Semenyih Water Treatment Plant. Samples of low to high turbidities from two different rivers in Malaysia were collected and compared with the existing coagulant (liquid alum) that is being widely used by the treatment plants. The performance of S.S-g-PAml were found to be good as compared to liquid alum with the advantages of the biodegradability of S.S-g-PAml as well as less dosage of S.S-g-PAml used as compared to liquid alum.